Batch Studies On Arsenic Adsorption Onto Lignite, Bentonite, Shale And Iron Sand: Effects Of Ph, Time, Particle Size And Sulfate Concentration - Kyu Kyu Mar; Dwikorita Karnawati; Doni Prakasa Eka Putra; Sarto Sarto; Toshifumi Igarashi; Carlito Baltazar Tabelin (Journal of Applied Geology, 2015)
Arsenic (As) is a toxic element found in both natural and anthropogenic sources. High concentration of this element was recently uncovered in the groundwater of Sumbawa Island, Indonesia. To mitigate this problem, As adsorption potential of natural geological materials like lignite, bentonite, shale, and iron sand obtained in Indonesia were evaluated by batch experiments. Arsenic adsorption onto these materials was investigated as a function of solution pH, particle sizes of adsorbents and coexisting sulfate concentration. In addition, batch leaching experiments were performed to elucidate the stability of geogenic As present in all adsorbents at different pHs. The results showed that among these natural materials tested, lignite was the most effective adsorbent of As(V) followed by bentonite, shale and then iron sand, and that the amounts of As(III) adsorbed onto all adsorbents were lower than those of As(V).This indicates that As(III) is more mobile in comparison to As(V). The adsorption isotherms of As(III) and As(V) conformed to nonlinear types, either Langmuir or Freundlich. It was found that adsorption of As onto these natural adsorbents was pH-dependent. This could be attributed to the changes in the surface charges of the adsorbents with pH. With respect to the adsorbent particle size, the amount adsorbed somewhat increased with decreasing particle size, which could be explained by the larger surface area of the smaller particles. Acidic (pH < 6) and alkaline (pH >10) conditions destabilized the geogenic As content of the adsorbents, indicating that the effectiveness of these natural materials as adsorbents is greatly limited by the pH of the contaminated system. Keywords: Adsorption, arsenic, natural geological materials, particle size, pH